Implementing Access to Justice For Persons With Disabilities in The Bantul Religious Court - Fajar Fauzani; Francisca Romana Harjiyatni (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2026)
Access to justice for persons with disabilities in Indonesia’s Religious Courts remains underexplored, even though national legislation and the Convention on the Rights of Persons with Disabilities (CRPD) require disability-inclusive proceedings. This study examines how disability-related access-to-justice norms are implemented in the Bantul Religious Court, identifies the factors that enable or hinder their implementation, and assesses the extent to which current practice conforms to the applicable legal framework. The article plays an exploratory and evaluative role by providing one of the first empirical socio-legal portraits of a religious court that has begun to institutionalize accommodation for persons with disabilities. Data were generated through qualitative empirical legal research: semi-structured interviews with judges, court staff, and ‘Sentra Advokasi Perempuan, Difabel dan Anak’ (SAPDA) representatives; courtroom and facility observation; and analysis of relevant regulations, Standard Operating Procedures, and case documents. Discussion combines descriptive mapping of infrastructure, procedures, and services with normative-empirical analysis against national and international standards. The findings show that Religious Court Bantul has introduced concrete accommodations, including the ‘Siap Antar Jemput Kembali Disabilitas’ (SIANJELITA) transport service, innovation of audio-visual communication channel between judges and disabled parties (deaf and mute) called CHITATA, disability-friendly physical facilities, and structured collaboration with SAPDA. At the same time, gaps persist in early disability screening, continuity of disability-competence training, availability and maintenance of assistive devices, provision of accessible information (such as Braille and screen-reader-compatible content), and disability-sensitive legal aid and complaint mechanisms. The article identifies Religious Court Bantul as a transitional model moving beyond formal compliance toward transformative equality. It outlines priority reforms and research agendas needed to consolidate an inclusive access-to-justice framework within the religious court system.